Joint-Venture Universities in China: Shanghai and Shenzhen Comparisons - Hayhoe, Ruth; Pan, Julia (International Higher Education, 2015)
This article illustrates two features of emerging joint venture universities in China, the requirement of formal partnership between a Chinese and a foreign university, and the substantial financial provision made for these new institutions by towns and cities in the Eastern Coastal region. Contrasts in curricular scope and the potential for attracting excellent faculty on a long-term basis are made between established British and American partnerships in the Shanghai area and emerging institutions in the southern city of Shenzhen.